The Importance of Cooperation for Innovation in the Region - Niki Derlukiewicz; Anna Mempel-Śnieżyk (Barometr Regionalny, 2018)
The paper considers the issue of cooperation between particular actors such as: enterprises, local government, R&D sector, and business environment institutions in the context of innovativeness of the economy. Presently, numerous studies analyze how to create an innovative economy in order to answer the question of what contributes to generation of innovations and the key elements in this process. Furthermore, the created models of a group of determinants influencing innovativeness are still evolving and depending on the examined aspect, different approaches to innovation in the regions are presented, including cooperation between the aforementioned entities. The main aim of the paper is to present the significance of cooperation between different actors in the region for developing innovative solutions. To achieve the aim, the authors present an example of cooperation between enterprises, pointing out the benefits of common projects, and present activities undertaken in regions which enhance innovation. The authors also focus on checking the offers and readiness for cooperation of selected Polish universities. In order to elaborate the basic information, the authors conducted desk and field research. In order to check the state of the art of the investigated issue and prepare the background for the empirical part of the paper, analysis of the literature on the subject was conducted. The desk research was supported by Google Scholar, Emerald, and Scopus databases. To present cooperation in the regions in the context of innovativeness, the authors used the method of observation and case studies. As a result of the research, it can be said that cooperation between science and business brings mutual benefits, although when the benefits to businesses are often analyzed and measured in the literature on the subject, less attention is paid to the effects of cooperation for the R&D sector — e.g., financing the scientific research by the business sector, and the opportunity for scientific workers to gain experience in enterprises. According to the conducted research it can be said that the last two decades brought changes both in the awareness of local authorities about their role in creating a pro-innovative environment and in the way they operate. Polish universities have also started transformation and have started to deal with potential co-operators by preparing the offer and information for them.